Theoretical and experimental analysis of applicability of sill with different widths on the gate discharge coefficients - Rasoul Daneshfaraz; Reza Norouzi; Hamidreza Abbaszadeh; Hazi Mohammad Azamathulla (Water Supply, 2022)
In this study, the effects of the gate opening, sill placement with different widths under the gate, and the sill position from under the gate on the discharge coefficient were investigated experimentally. Sills are placed in positions below, tangentially and upstream of the gate at distances of 7.5 and 17.5 cm from the gate. The results of the present study showed that the discharge coefficient increases with increasing sill width and decreasing total area of the flow passing through the gate. The discharge coefficient increases by installing the sill at certain intervals at increasing distance with respect to the upstream of the sluice gate and has a lower value compared to the non-sill state. At the same opening in non-sill and suppressed sill states, with a sill below and tangential to the gate, the discharge coefficient of the sluice gate with the sill has increased compared to the non-sill state. In addition, the discharge coefficient for a tangential sill has the highest value. HIGHLIGHTS Experimental investigation of the sluice gate discharge coefficient without and with sills in different widths and positions has been done.; A general equation for calculating the flow rate passing through the sluice gate in suppressed sills was developed for non-suppressed sills.; This investigation improves the design of hydraulic control structures.;